A comprehensive study of NGC 2023 with XMM–Newton and Spitzer - López García, M. A. (2013)
Nearby star-forming regions are ideal laboratories to study high-energy emission of different stellar populations, from very massive stars to brown dwarfs. NGC 2023 is a reflection nebula situated to the south of the Flame Nebula (NGC 2024) and at the edge of the H II region IC 434, which also contains the Horsehead Nebula (Barnard 33). NGC 2023, NGC 2024, Barnard 33 and the surroundings of the O-type supergiant star ζ Ori constitute the south part of the Orion B molecular complex. In this work, we present a comprehensive study of X-ray emitters in the region of NGC 2023 and its surroundings. We combine optical and infrared data to determine physical properties (mass, temperature, luminosity and the presence of accretion discs) of the stars detected in an XMM–Newton observation. This study has allowed us to analyse spectral energy distribution of these stars for the first time and determine their evolutionary stage. Properties of the X-ray emitting plasma of these stars are compared to those found in other nearby star-forming regions. The results indicate that the stars that are being formed in this region have characteristics, in terms of physical properties and luminosity function, similar to those found in the Taurus–Auriga molecular complex.